Diversity and conservation threats of water birds in and around Barandabhar corridor forest, Chitwan, Nepal - Adhikari, Jagan Nath; Bhattarai, Bishnu Prasad; Thapa, Tej Bahadur (Journal of Natural History Museum, 2018)
Wetlands provide major ecological services for feeding and breeding places of a large number of water birds in many parts of the globe and also play a vital role in conservation of threatened species. Wetlands in Nepal support a total of 27% of nationally threatened birds. Barandabhar forest is only one vertical (south-north) bio-corridor that links two different ecosystems, CNP and the Mahabharat hill range. Eight wetlands were selected for water birds monitoring by using area search and point count methods to explore the diversity and conservation threats of water birds in Barandabhar corridor forest. This study recorded 3664 individuals of water birds belonging to 54 species, 11 orders and 13 families in which the highest numbers of the species were belonged to order Passeriformes (17 species). The diversity of water birds in eight different wetlands showed the highest diversity in Rapti river (H= 3.403), followed by Beeshazari lakesystem (H= 3.401), Batulpokari lake area (H= 3.377) and the rest of others. The least diversityof water birds was found in Gundremandre lake (H=2.210). Similarly, the species dominance was more in Gundremandre lake (D=0.189) than Beeshazari (D=0.046) and Batulpokhari (D=0.042). The species richness in various habitats association with wetlands showed that Shorea forest association was utilized very less as compared to its availability. Fishermen (r= -0.391, t = 10.6, P<0.0001) and livestock pressure (r = -0.276, t = 6.63, P = 0.0009) caused the significant negative impact on the occurrence of water birds in many parts of the study sites. The study suggests that annual flooding in the rivers (e.g., Rapti, Budhirapti and Khageririvers), human disturbance (e.g., livestock grazing and fishing), habitat loss and degradation, declining water quality and quantity caused by eutrophication and chemical pollution are the major threats of water bird communities in Barandabhar corridor forest.